Pengaruh Motivasi Kerja, Disiplin Kerja Dan Pengembangan Karier Terhadap Kinerja Guru (Studi Pada Yayasan Taman Pendidikan Al-Islam Wahid Hasyim Malang) - Ahmad Fauzan; Muhammad Ridwan Basalamah; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of work motivation, work discipline and career development on the performance of study teachers at the Wahid Hasyim Al-Islamic Park Foundation, Malang. The type of research used is quantitative research with the method of distributing questionnaires. The sample in this study were 40 respondents and data processing using the SPSS computer program. This study has met the requirements of validity and reliability. The data analysis used in this study is the classical assumption test, multiple linear regression, hypothesis testing and coefficient of determination analysis. The variables used in this study are teacher performance variables (dependent variable), while the independent variables are work motivation, work discipline and career development.The results of the analysis show that work motivation, work discipline and career development simultaneously have an effect on teacher performance, partially work motivation and career development have no effect, but work discipline has an influence on teacher performance at the Wahid Hasyim Al-Islamic Garden Foundation Malang. Keywords: Work Motivation, Work Discipline, and Career Development on Teacher Performance